2021
DOI: 10.1088/1748-9326/abf60b
|View full text |Cite
|
Sign up to set email alerts
|

Mortality-based damages per ton due to the on-road mobile sector in the Northeastern and Mid-Atlantic U.S. by region, vehicle class and precursor

Abstract: On-road vehicular emissions contribute to the formation of fine particulate matter and ozone which can lead to increased adverse health outcomes near the emission source and downwind. In this study, we present a transportation-specific modeling platform utilizing the community multiscale air quality model (CMAQ) with the decoupled direct method (DDM) to estimate the air quality and health impacts of on-road vehicular emissions from five vehicles classes; light-duty autos, light-duty trucks (LDT), medium-duty t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Despite multiple policies addressing fuel switching and technology changes, emissions remain high enough to impact the city’s population. In the past decade, multiple studies focused on PM 2.5 pollution in NYC, including concentration trends 11 15 , 22 source apportionment, 16 , 17 health burden, 18 23 and emission control. 25 , 26 Despite declines in PM 2.5 concentrations (New York City Community Air Survey (NYCCAS) 27 2019 and U.S. EPA monitoring observations from 2011 to 2020), the health burden attributed to current ambient levels of PM 2.5 is still high enough to be of concern.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite multiple policies addressing fuel switching and technology changes, emissions remain high enough to impact the city’s population. In the past decade, multiple studies focused on PM 2.5 pollution in NYC, including concentration trends 11 15 , 22 source apportionment, 16 , 17 health burden, 18 23 and emission control. 25 , 26 Despite declines in PM 2.5 concentrations (New York City Community Air Survey (NYCCAS) 27 2019 and U.S. EPA monitoring observations from 2011 to 2020), the health burden attributed to current ambient levels of PM 2.5 is still high enough to be of concern.…”
Section: Introductionmentioning
confidence: 99%
“…Traffic emissions from the New York Metropolitan Statistical Area (NYMSA) were estimated to have caused ∼1800 premature deaths due to exposure to PM 2.5 and O 3 , with 20% due to emissions from medium-duty trucks (MDT) and 17% due to the heavy-duty trucks (HDT) sector. 11 Jin et al 29 used multiple estimates of PM 2.5 exposures for New York state from varying techniques (satellite remote sensing, air quality modeling, land use regression modeling, etc.) and assess gains in air pollution-related health benefits for a decadal period and state a 28% uncertainty because of choice of different techniques for estimating air pollution levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also several possible reasons. Researchers found that a decrease in PM 2.5 can lead to an increase in the O 3 concentration [62,63] because PM 2.5 can eliminate the precursors of ozone, including hydroxyl radicals and nitrogen-oxygen free radicals [64,65]. When the PM 2.5 concentration falls, the concentrations of hydroxyl radicals and nitrogen-oxygen free radicals in the air will increase, thereby promoting the production of ozone [66].…”
Section: Heterogeneity Analysis Of Five Pollutantsmentioning
confidence: 99%